KEDUDUKAN MAJELIS PERMUSYAWARATAN RAKYAT DALAM PEMAKZULAN PRESIDEN MENURUT UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - , Sugeng Riyadi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The Republic of Indonesia Constitution of 1945 arranged Peopleâs Consultative Assembly supremacy system. As a high state institution, the Assembly has a high position of all other state institution. Then, this position changed followed the Amendment of The Republic of Indonesia Constitution of 1945. Now, according to The Republic of Indonesia Constitution of 1945 (amendment), Peopleâs Consultative Assembly position is in the same degree with another state institution like the House of Representative (DPR), President, Supreme Court (MA), and another state institution. Although its position has changed, as representative institution, the Peopleâs Consultative Assembly still has power to dismiss or not president and/or vice president. That power sharing is seen not be integrated with the cohesiveness consideration of parliament system will be chosen. That is can be seen on absence of practice of checks and balances concept between representative institution like there is no role played by Regional Representative Council (DPD). That power grant gives Peopleâs Consultative Assembly opportunity to break of law. Because, Peopleâs Consultative Assembly can ignore Verdict of Constitutional Court that confirming indictment of the House of Representative concerning either when president and/or vice president proven guilty of violating the law by betrayal of the state, of corruption, of bribery, of any other felony, or because of disgraceful behavior, as well as when proven no longer to fulfill the conditions as president and/ or vice president. It is clear that scheme not compatible with presidential system that emphasizes just law reasoning to impeach president and/or vice president. Mechanism of presidential impeachment will be appeared to be aligned with the idea presidential system of government if we only observe the early process of impeachment that have been using reasoning of law. But if we observe all of process of impeachment, so mechanism of presidential impeachment isnât yet in accordance with this concept, because distribution role in presidential impeachment proceedings isnât yet in accordance with check and balance concept between states organs that is âcoreâ of presidential system.